LEVEL OF KNOWLEDGE ON MAINTENANCE OF TEETH AND MOUTH CLEANLINESS WITH AUDIO MEDIA AND BRAILLE LEAFLET MEDIA IN BLIND CHILDREN IN SLB N SEMARANG - Kurnia Aprianti (Journal of Applied Health Management and Technology, 2022)
ABSTRACTDental health education is a learning process aimed at individuals and community groups to achieve the highest degree of community dental health. The problem is that blind children need the right media to increase knowledge of dental and oral health. Blind children use the sense of touch and hearing as a substitute for the sense of sight in the learning process. The purpose of the study was to see the level of knowledge on how to maintain oral hygiene in blind children with counseling using audio media andleaflet media braille. This study uses an interventional analytic design with research subjects 24 blind children at SLB N Semarang using audio media andleaflet media braille. The data that has been obtained were analyzed using thestatistical Wilcoxon Test and Mann Whitneytests. Statistical test with Wilcoxon Test showed a significant difference withvalue p 0.003 between before and after counseling with audio media and there was a significant difference p 0.002 between before and after counseling withleaflet media braille. The Mann Whitney Test was used to see the level of knowledge of the two media, in this study showed a difference in the level of knowledge with avalue of p 0.001 between the counseling group with audio media andleaflet media braille. According to the results of the, it can be concluded that there is a difference in the level of knowledge on how to maintain oral and dental hygiene in blind children, where audio media counseling increases their knowledge more thanleaflet media counseling braille.